A criança na fotografia: o retrato da infância na primeira metade do século XX em Belém do Pará (1900 a 1950) - NASCIMENTO, Sebastião Valério Silveira do (Universidade Federal do Pará, 2013)
The present study aims to examine the childhood photograph of children in the city of Belém do Pará in the first half of the twentieth century. Therefore, the research focuses on the importance of photography as a historical document that reveals multiple meanings; matter, especially its potential as language or representative of childhood and of a conception of childhood scenario built in the city of Belém do Pará, which comprises the first half of the twentieth century. The photograph is a historical source, is an image / document. In the case of photos for the family album, has a record of family history and family member, not necessarily to be within an album, but only to present such characteristics as literally reveal the ways and circumstances in which the family or part of it is photographed. Have photos of children in magazines, are displacements of the photos that were usually produced for own family's interest to put them on their albums, however, were also used as a means of promoting family loose inside publications in journals or periodicals of the first decades twentieth century. Usually accompanied by a message discursive bringing the "name" of the family. The photograph allows almost everyone (not just the wealthy) can become object-image, or a series of images that depict moments of their lives. In this case, the images found in albums of school celebrations are proof of that: photographs of children exclusively and for commemorative purposes with some annual events present in children's educational leisure. The photograph could be taken as an equivalent of individual and collective memory, with the image of a fixed time, apparently, was "clipped". The photograph of children in journals and family album is a way to understand and meet the social, cultural and educational childhood in the Amazon because the images can reveal many indexes about a family and, by extension, society : their rites, ways of life, affection and ideals. The research corpus is composed of photographs of children archived in the Library Arthur Viana. For further theoretical about photography and image utilize Dubois, Kossoy, Benjamin, Fabris, Milk, Mauad, Burke and Fischman. As for reading about childhood highlight Rizzini, Del Priori, Freitas, and Kulmman. In the context of the reality of the Amazon privilege the following authors: Bezzera Neto and Sarges.